Intention of commencing Master of Nursing Sciences programme in Macau. - Wen Z; Leung L; Kio VI (Macau Journal of Nursing, 2007)
Objective: To study the intention among Bachelor of Science in Nursing (BSN) graduates, BSN undergraduates of commencing Master of Nursing Sciences (MNS) in Macau. Method: A non-experimental and descriptive study methods were adopted, and questionnaires of ‘Survey on Intention of Commencing Master of Nursing Sciences in Macau’ were distributed to the BSN graduates, BSN graduates. Result: There were 619 nurses and nursing students including 424 (68.5%) in-service nurses and 195 (31.5%) nursing students completed the questionnaires. The majority (84.5%) indicated a need to commence the MNS in Macau at present. 57.8% of the respondents expressed that they would pursue the MNS. The top three desirable areas are ‘Psychological Nursing’ (50.1%), ‘Community Nursing’ (47.3%) and ‘Nursing Management’ (46.4%). The desires of commencing the MNS of 174 (92.1%) nursing students were obviously stronger than the in-service nurses (81.1%). The will of 157 (83.1%) nursing students pursuing the MNS was also obviously stronger than the in-service nurses (46.5%). Conclusion: There is an urgent demand for running the MNS in Macau. These also provide certain scientific evidence for running the MNS in future.